Epidemiological study of the evolution of the number of cases and the cost of hospitalization due to burns and corrosions in children in brazil (2010 - 2019) - Bezerra, Thalia Amaro de Souza; Holanda, Lucas Oliveira; Pacífico, Arthur Antunes Coimbra Pinheiro; Amaral, Giana Lobão; Correia, Aline Santos (Seven Editora, 2023)
The epidemiological study on burns allows guiding new prevention and care strategies through scientific basis, while analyzing variables that contribute to morbidity and mortality. Objective: The aim of this article is to conduct an epidemiological study about the evolution of the number of cases and the cost of hospitalization for burns and corrosions in children in Brazil from 2010 to 2019. Method: This is a cross-sectional, documentary study and has a quantitative approach, with data comprising epidemiological information of hospital morbidity and mortality and health indicators located in the period from January 2010 to December 2019, which were collected through the SUS Hospital Morbidity Declaration System of DATASUS. Results: The number of notifications for burns and corrosions in children in the period between 2010 and 2019, with a total of 72,177 cases. When comparing the data from 2010 and 2019, there was a 19.02% decrease in the number of cases in the pediatric age group. It is noteworthy that the group of children aged 1 to 4 years represents 63.85% of the total sample. There is a higher percentage of occurrences in males, which represent 60.28% of the sample.  The Northeast region had the highest number of cases with 36.5% (26,352 cases) of the sample, while the North region represented only 8.12% (5,865 cases) of the sample. The Southeast region showed the highest mean cost (R$1,935.88), in contrast to the North region, which showed a mean cost of only R$1,227.63. Conclusion: By analyzing the age range in question, one can relate the causes of the occurrence of burns to age-related risk behaviors and propagated cultural values that expose male children more prominently to the dangers. It is worth mentioning that the socioeconomic profile of the regions also interferes in the number of occurrences, notifications and in the investment in material and human resources directed to these services. DOI:https://doi.org/10.56238/devopinterscie-265